RELEVANSI ANTARA PENOLAKAN RISALAH NABI MUHAMMAD SAW DENGAN PENOLAKAN PERUBAHAN BATASAN USIA PERKAWINAN - Taufikur Rohman; Nasta'in Nasta'in (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This paper analyzes the relevance between rejecting the Prophet Muhammad’s SAW monographic and rejecting the marriage limitation age. It has qualitative research for data, books, and articles. They contain Muhammad saw monographic and revision of the marriage limitation age. This research continues the topic of the relevance between rejecting the Prophet Muhammad SAW monographic and rejecting the marriage limitation age. We can see from the results that there is relevance. Both reject revisions and keep freshness. But both understand the revision. Unbelievers don’t understand that Muhammad’s SAW lesson was a truth for life and hereafter. Meanwhile, other people reject the revisions because they need to learn the effects a lot